Activities Formulation of Jackfruit (Artocarpus Heterophyllus Lamk) and Moringa (Moringa Oleifera) Leaf on Antidiabetic in Vivo - Joko Santoso; Atiek Murhayati; Irma Erinda Nur Pratiwi (Jurnal Farmasi (Journal of Pharmacy), 2021)
Indonesia ranks sixth in the world for the highest prevalence of diabetes after China, India, the United States, Brazil, and Mexico. The prevalence of people with diabetes in Indonesia tends to increase, where in 2007 it was 5.7% and in 2013 it was 6.9%. In 2045, the number is estimated to be 16.7 million people with diabetes aged 20-79 years. Jackfruit leaves (Artocarpus heterophyllus Lamk) contain phytochemical compounds, active compounds of flavonoids, tannins, saponins, alkaloids, polyphenols, steroids, where these compounds can reduce blood glucose levels. Jackfruit leaves and Moringa leaves contain flavonoids, tannins, alkaloids, triterpenoids, saponins, and reducing sugars showed that flavonoids have a hypoglycemic effect. Objective To evaluate the activity of the jackfruit and moringa leaf formulations against antidiabetic in vivo. Methods The research used experimental methods with a post test design laboratory research approach where this study was divided into 5 experimental groups, each group consisting of 5 test animals. Results: Tests for blood sugar levels in rats were Group I (ENK 200mg/kgBW) of 110.30 mg/dL, Group II (ENK 400mg/kgBW) of 100.50 mg/dL, Group III (ENK 800mg/KgBW) of 95.50 mg/dL, Group IV (Glibenclamide 150mg/KgBW) of 120, 30 mg/dL and Group V (Aquadest) of 190.30 mg/dL. Conclusion: The effective dose and activity as antidiabetic is group III ( ENK 800mg) because it can reduce blood sugar levels by 95.50 mg/dL compared to other groups.Keywords: Jackfruit leaves, Moringa and Antidiabetes